From Interpersonal Vulnerability to Behavioral Risk: A Multilevel Model of Adolescent Suicide Attempts in a School-Based Population - Gaudencio C. Aljibe Jr; Michael J. Froilan (Public Health, 2026)
Adolescent suicide attempts represent a critical public health concern shaped by interacting behavioral, interpersonal, and institutional risk factors. This study examined multilevel determinants of suicide attempts among 30,226 secondary school adolescents in the Northern Samar Division of the Philippines using a quantitative cross-sectional design aligned with the World Health Organization (WHO) Global School-based Student Health Survey (GSHS) framework [1]. Data were collected through an anonymous structured online survey assessing substance use, dietary behaviors, peer and family connectedness, school engagement, lifestyle regulation, and bullying victimization. Hierarchical binomial logistic regression was conducted to estimate adjusted associations, with model performance evaluated using deviance statistics, pseudo-R², and area under the receiver operating characteristic (ROC) curve. Suicide attempts were reported by 14.10% of respondents. The final model demonstrated strong explanatory capacity (Nagelkerke R² = .259) and good discrimination (AUC = .795), with overall classification accuracy of 75.3%. Substance-related variables showed significant associations, particularly lifetime cannabis use (OR = 5.56, p < .001), frequent alcohol use (OR = 1.85, p < .001), and high sugar-sweetened beverage consumption (OR = 1.81, p < .001). Relational factors were among the strongest predictors, with adolescents reporting rare or no parental understanding showing nearly threefold increased odds (OR ≈ 3.0, p < .001). Lifestyle dysregulation variables, including short sleep duration (<5 hours; OR = 1.93, p < .001) and high sedentary time (OR = 1.68, p < .001), were also significant. Bullying victimization, particularly cyberbullying (OR = 2.19, p < .001), independently predicted suicide attempts. These findings support an integrated vulnerability model in which substance exposure, relational disconnection, behavioral dysregulation, and victimization jointly elevate suicide risk. Multicomponent school-based prevention strategies addressing these domains are essential for reducing adolescent suicide attempts.